2014
DOI: 10.1108/ijqrm-04-2013-0070
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of Lean Six Sigma implementation in SMEs – a migratory perspective

Abstract: Purpose – The purpose of this paper is to investigate the migratory nature of Lean Six Sigma (LSS) implementation and adoption in manufacturing-based SMEs in the UK. The companies were surveyed at two points over a five-year period. These periods were before and after the 2008 recession point. This being done in order to identify the level of LSS adoption as a result of the tougher economic climate that has prevailed since 2008. Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…This research study has been undertaken through rigorous primary data collection in German manufacturing SMEs and has responded to the call for more empirical work to be done within the LSS implementation area of the literature (Shokri et al, 2014;Thomas et al, 2014;Zhang et al, 2012;. The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011).…”
Section: Research and Practical Implicationssupporting
confidence: 79%
See 1 more Smart Citation
“…This research study has been undertaken through rigorous primary data collection in German manufacturing SMEs and has responded to the call for more empirical work to be done within the LSS implementation area of the literature (Shokri et al, 2014;Thomas et al, 2014;Zhang et al, 2012;. The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011).…”
Section: Research and Practical Implicationssupporting
confidence: 79%
“…The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011). In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation.…”
Section: Research and Practical Implicationssupporting
confidence: 77%
“…With regard to lean perception, the survey indicates that North African SMEs feel the urgent need for such initiative. However, they are still viewing lean as a “Toolbox for Productivity/Quality improvement” rather than an “Integrated system for continuous improvement.” Thomas et al () came to the same conclusion in the United Kingdom and stated that Lean Six Sigma (LSS) is still seen by SMEs as an operations improvement methodology rather than a complete business improvement strategy. This is explicated by the lack of understanding of the real essence of the lean philosophy (Khan, Bali, and Wickramasinghe ; Rose, Deros, and Rahman ).…”
Section: Discussion and Insights Of Resultsmentioning
confidence: 91%
“…However, this conclusion cannot be generalized to other countries. For example, Thomas et al (2014) have not found a similar level of understanding of lean six sigma among SMEs in the United Kingdom, which still considers it as an operations improvement methodology rather than a complete business improvement strategy. Several authors (Khan, Bali, and Wickramasinghe 2007;Kumar and Antony 2008) came to the same conclusion in the U.K. environment.…”
Section: Perception Of Lean Implementation Bymentioning
confidence: 99%
“…LSS has been widely associated with large manufacturing firms like Motorola, who was the first to introduce the concept of Six Sigma. Reasons for implementing Lean Six Sigma include reducing defects and contributing to financial savings (Vinodh et al, 2014), remaining economically competitive (Thomas et al, 2014), improving process quality and improving services to customers (Carsten, et al, 2015). Lean and Six Sigma began as two distinctly different methodologies.…”
Section: Introductionmentioning
confidence: 99%